2022
DOI: 10.17798/bitlisfen.1082417
|View full text |Cite
|
Sign up to set email alerts
|

Mimar Sinan Camilerinde Sütunların Formları, Dikey ve Yanal Yük Kapasiteleri

Abstract: Along with the walls, columns are the main load-bearing elements in carrying vertical and horizontal loads in most historic masonry buildings. When the mosques of Mimar Sinan, the great Ottoman architect, are examined, it is seen that there is a wide variety in column forms. Motivated by this situation, in this study, the column forms in Sinan's a few mosques were investigated, their geometric dimensions were measured, and the vertical and lateral load carrying capacities of them were determined. The columns e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…At the end of the study, the maximum and minimum displacement values for the critical structural members were examined. Bayraktar et al [24] determined analytical and experimental vibration parameters of a historical twospan bridge built in the 19th century and located in northern Turkey. Comparing the natural frequency, mode shapes, and damping rates for analytical and experimental results, the authors observed slight differences.…”
Section: Introductionmentioning
confidence: 99%
“…At the end of the study, the maximum and minimum displacement values for the critical structural members were examined. Bayraktar et al [24] determined analytical and experimental vibration parameters of a historical twospan bridge built in the 19th century and located in northern Turkey. Comparing the natural frequency, mode shapes, and damping rates for analytical and experimental results, the authors observed slight differences.…”
Section: Introductionmentioning
confidence: 99%